Psychoanalysis and the unconscious and fantasia of the unconscious - Lawrence, David Herbert, 1885-1930. (Cambridge ; New York)
liv, 300 s.
Keywords: "Written in D. H. Lawrence's most productive period, 'Psychoanalysis and the Unconscious' (1921) and 'Fantasia of the Unconscious' (1922) were undertaken initially in response to psychoanalytic criticism of his novel Sons and Lovers. They soon developed more generally to propose an alternative to what Lawrence perceived as the Freudian psychoanalytic theory of the unconscious and the incest motive. The essays also develop his ideas about the upbringing and education of children, about marriage, and about social and even political action. Lawrence described them as 'this pseudo-philosophy of mine which was deduced from the novels and poems, not the reverse. The absolute need one has for some sort of satisfactory mental attitude towards oneself and things in general makes one try to abstract some definite conclusions from one's experiences as a writer and as a man'. These conclusions form an illuminating guide to his works and therein lies their peculiar value." --